Design of Disposal Area Transition and Drainage at Pit 2AA PT Sentosa Laju Sejahtera Site CV Anggaraksa Adisarana Loa Janan - Suparno, Fanteri Aji Dharma; Ariadi, Arda Bara; Irawan, Januar Fery; Aminah, Siti; Haeruddin; Rini, Utari Retno Sulistyo; Mulyani, Kurnia Dewi; Manek, Emanuel Grace (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
This research discusses the design of the disposal area transition and drainage system in Pit 2AA of PT Sentosa Laju Sejahtera to overcome the limited space of the stockpile due to the use of the backfilling method. The main issues include effective drainage design, selection of alternative disposal sites, and embankment slope stability analysis. The planned rainfall was calculated using the Gumbel distribution with rainfall data for the last 10 years (2014-2023), while the runoff water discharge was calculated using the Rational method, resulting in a discharge of 7.8 m³/second. The open channel was designed with two trenches, Trenches A and B, with capacities of 9.59 m³/sec and 7.92 m³/sec, respectively. The disposal design was placed outside the Life of Mine boundary, using the gradual finger disposal method with three levels from elevation 93 to 105 meters. The slope geometry consists of a tier height of 4 meters, a tier width of 15 meters, a single slope angle of 30°, and an overall slope of 13°. The total disposal capacity reached 441,310 BCM. Slope stability analysis was conducted using the Janbu Simplified method, showing that the factor of safety (FK) value is in the range of 1.308-2.404, meeting the minimum FK ≥ 1.3 according to the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018. The results show that the drainage and disposal designs are technically feasible and support the sustainability of mine operations.